Favourable metabolic effects of a eucaloric lower‐carbohydrate diet in women with PCOS. (20th May 2013) - Gower, Barbara A.; Chandler‐Laney, Paula C.; Ovalle, Fernando; Goree, Laura Lee; Azziz, Ricardo; Desmond, Renee A.; Granger, Wesley M.; Goss, Amy M.; Bates, G.Wright
Summary: Objective: Diet‐induced reduction in circulating insulin may be an attractive nonpharmacological treatment for women with polycystic ovary syndrome (PCOS) among whom elevated insulin may exacerbate symptoms by stimulating testosterone synthesis. This study was designed to determine whether a modest reduction in dietary carbohydrate (CHO) content affects β‐cell responsiveness, serum testosterone concentration and insulin sensitivity in women with PCOS. Design: In a crossover design, two diets ('Standard, ' STD, 55:18:27% energy from carbohydrate/protein/fat; lower‐carbohydrate, 41:19:40) were provided for 8 weeks in random order with a 4‐week washout between. Patients: Thirty women with PCOS. Measurements: β‐cell responsiveness assessed as the C‐peptide response to glucose during a liquid meal test; insulin sensitivity from insulin and glucose values throughout the test; insulin resistance (HOMA‐IR); and total testosterone by immunoassay. Results: Paired t ‐test indicated that the lower‐CHO diet induced significant decreases in basal β‐cell response (PhiB), fasting insulin, fasting glucose, HOMA‐IR, total testosterone and all cholesterol measures, and significant increases in insulin sensitivity and dynamic ('first‐phase') β‐cell response. The STD diet induced a decrease in HDL‐C and an increase in the total cholesterol‐to‐HDL‐C ratio. Across all data combined, the change in testosterone was positively associated with the changes in fasting insulin, PhiB and insulin AUC ( P < 0·05). Conclusions: In women with PCOS, modest reduction in dietary CHO in the context of a weight‐maintaining diet has numerous beneficial effects on the metabolic profile that may lead to a decrease in circulating testosterone.